2008
DOI: 10.1152/ajpgi.90372.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting intestinal NPC1L1 activity prevents diet-induced increase in biliary cholesterol in Golden Syrian hamsters

Abstract: Niemann-Pick C1-like 1 (NPC1L1) facilitates the uptake of sterols into the enterocyte and is the target of the novel cholesterol absorption inhibitor, ezetimibe. These studies used the Golden Syrian hamster as a model to delineate the changes in the relative mRNA expression of NPC1L1 and other proteins that regulate sterol homeostasis in the enterocyte during and following cessation of ezetimibe treatment and also to address the clinically important question of whether the marked inhibition of cholesterol abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 50 publications
6
52
1
1
Order By: Relevance
“…The current studies confi rm and extend prior studies that report increased LDLR and HMGR mRNAs in the intestines of miniature pigs, hamsters, and mice in response to ezetimibe, as well other reports that in vivo sterol synthesis rates in the intestine are increased by ezetimibe in hamsters and mice ( 39,47,54 ). Ezetimibe has also been shown to increase whole-body fractional LDL clearance as estimated by apoB kinetics in miniature pigs and humans ( 54,55 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current studies confi rm and extend prior studies that report increased LDLR and HMGR mRNAs in the intestines of miniature pigs, hamsters, and mice in response to ezetimibe, as well other reports that in vivo sterol synthesis rates in the intestine are increased by ezetimibe in hamsters and mice ( 39,47,54 ). Ezetimibe has also been shown to increase whole-body fractional LDL clearance as estimated by apoB kinetics in miniature pigs and humans ( 54,55 ).…”
Section: Discussionsupporting
confidence: 88%
“…This fi nding agrees with prior studies that reported decreases in the intestinal expression of ABCA1, ABCG5, and ABCG8 in response to ezetimibe in multiple species ( 47,48 ). Although the mechanism for this effect is unclear, the reduced sterol fl ux associated with NPC1L1 blockade may reduce the availability of endogenous LXR ligands.…”
Section: Ezetimibe Suppresses Idol An Lxr-responsive Degrader Of Ldlrsupporting
confidence: 91%
“…The pathways explored in animal studies are very similar to those operating in man and undoubtedly help in understanding the compensatory processes in man (19)(20)(21). These studies indicate that there is an increase in cholesterol synthesis in the liver and perhaps more importantly, in the intestinal tract.…”
Section: Discussionmentioning
confidence: 76%
“…These studies indicate that there is an increase in cholesterol synthesis in the liver and perhaps more importantly, in the intestinal tract. In addition, there is an upregulation of hepatic LDL receptors (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Por el contrario, los niveles de ARNm de ABCG5 y ABCG8 cayeron significativamente en respuesta al tratamiento, retornando rápidamente a la normalidad una vez que fue cesada la administración de ezetimiba. En este estudio, además se constató un incremento en la expresión de la HMG-CoA reductasa como mecanismo compensatorio ante la disminución de colesterol (Valasek et al, 2008).…”
Section: Discussionunclassified